Nilai-Nilai Pendidikan Karakter Pada Siswa Perguruan Pencak Silat Bakti Negara Ranting Banyuning Kabupaten Buleleng - M.R. Bima; Ni Luh Putu Spyanawati; Peby Gunarto (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
This study aims to determine the process of instilling character education values in the members of the Bakti Negara Pencak Silat Association, Banyuning Branch, Buleleng Regency. This research is motivated by the importance of character education in facing the development of the times and the influence of globalization, which can affect the behavior of the younger generation. Pencak Silat, as both a sport and an Indonesian cultural heritage, is considered to have an important role in shaping character values such as discipline, responsibility, politeness, cooperation, and religiosity. The research method used was qualitative research with data collection techniques through observation, interviews, and documentation. The results showed that character education values had been implemented in the training process through activities such as time discipline, collective prayer, respect for trainers, and sportsmanship among members. However, several obstacles were still found, such as the lack of discipline of some members in following training rules. Therefore, continuous strengthening of character development is needed so that character education values can be optimally instilled in the members of the association.